2009
DOI: 10.1103/physreva.80.053612
|View full text |Cite
|
Sign up to set email alerts
|

Quantum many-body dynamics of dark solitons in optical lattices

Abstract: We present a fully quantum many-body treatment of dark solitons formed by ultracold bosonic atoms in one-dimensional optical lattices. Using time-evolving block decimation to simulate the single-band Bose-Hubbard Hamiltonian, we consider the quantum dynamics of density and phase engineered dark solitons as well as the quantum evolution of mean-field dark solitons injected into the quantum model. The former approach directly models how one may create quantum entangled dark solitons in experiment. While we have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 68 publications
4
77
0
Order By: Relevance
“…2,5,14,[54][55][56][57][58][59][60][61][62] Symmetries have also been used in more recent proposals to simulate time evolution with MPSs. [10][11][12][13][14][63][64][65][66][67][68] When considering symmetries, it is important to notice that an MPS is a trivalent tensor network. That is, in an MPS each tensor has at most three indices.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,14,[54][55][56][57][58][59][60][61][62] Symmetries have also been used in more recent proposals to simulate time evolution with MPSs. [10][11][12][13][14][63][64][65][66][67][68] When considering symmetries, it is important to notice that an MPS is a trivalent tensor network. That is, in an MPS each tensor has at most three indices.…”
Section: Introductionmentioning
confidence: 99%
“…The latter situation has been considered in Refs. [19,20] within many-body numerical calculations. Analysis of the second order correlation function leads the authors to the conclusion that a dark soliton cannot be observed when the single particle density becomes uniform.…”
mentioning
confidence: 99%
“…In one-dimensional (1D) space, this non-linear wave equation possesses a dark (bright) soliton solution if particle interactions are effectively repulsive (attractive). The GPE assumes all particles in the same single particle state and neglects that the interactions can populate other modes.There is a debate in the literature concerning manybody effects in a dark soliton [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The GPE predicts a stable dark soliton state in 1D.…”
mentioning
confidence: 99%
See 2 more Smart Citations